2020
DOI: 10.1080/23311975.2020.1787736
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of brand loyalty in the apparel industry: A developing country perspective

Abstract: The study aims to investigate the determinants of brand loyalty in the apparel industry of Botswana. A descriptive quantitative design was followed, and data were collected from respondents using a self-administered questionnaire. A structured equation modelling technique was used to validate the hypotheses. The results indicated an array of positive significant relationships between brand awareness, brand image, brand trust, and brand loyalty. Additionally, brand commitment significantly moderated the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
2
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 48 publications
4
12
2
9
Order By: Relevance
“…In addition, higher brand equity increases the level of consumer satisfaction, which eventually results in brand loyalty. The conclusions of this study conform to the findings of Kataria and Saini, (2019), Omoregie et al (2019), Alhaddad (2015), Ledikwe (2020), Keller (1993), Nam et. al.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, higher brand equity increases the level of consumer satisfaction, which eventually results in brand loyalty. The conclusions of this study conform to the findings of Kataria and Saini, (2019), Omoregie et al (2019), Alhaddad (2015), Ledikwe (2020), Keller (1993), Nam et. al.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Customers' knowledge regarding a specific product or brand shows them a certainty about the brand reliability, enhancing the level of brand trust (e.g., Chaudhuri & Holbrook, 2001). Brand knowledge component-brand image and brand awareness has an effect on brand trust (Ledikwe, 2020). The solid image is able to reduce the risk of perception and stimulate more familiarity with brand which, as a result, fosters the customers' trust (Lin & Lee, 2012;Alhaddad, 2015).…”
Section: Brand Knowledge and Brand Trustmentioning
confidence: 99%
“…La lealtad en tiempos pasados se la consideraba como el resultado de la repetición de compra (Ledikwe, 2020), sin embargo, esta misma involucra varios aspectos, como preferencias de marca, situaciones, experiencias vividas, entre otras, que hace que el adquiriente se convierta en un embajador de la marca. Kataria & Saini (2020), mencionan que la lealtad de marca puede tener dos dimensiones, la primera denominada conductual, misma que, consiste en la compra repetida sin mucho esfuerzo por parte de los consumidores o los esfuerzos que la competencia ejecute, la segunda es la lealtad actitudinal, la cual se refiere a una recompra en base a un apego emocional con la marca, misma que se da por recomendaciones, o incluso experiencias vividas al utilizar el bien o servicio.…”
Section: El Sector Retailunclassified
“…This result is substantiated by Altaf et al (2017), who found that the favorable perception of BA by clients will contribute to higher BI levels. The development of BA will then contribute to a higher degree of BI, allowing for greater profitability and greater market share (Algharabat et al, 2020;Ledikwe, 2020;Tran et al, 2019). Subsequently, it was hypothesized that:…”
Section: Impact Of Ba On Bimentioning
confidence: 99%